Profitability and resource use efficiency of rice seed production: A case of Chitwan, Nepal - Rabin Thapa; Shiva Chandra Dhakal; Sandip Subedi (Cogent Food & Agriculture)
Nepal’s food security is predominantly sustained by the production of cereal crops, with rice serving as the principal staple. Despite its socio-economic importance, the rice seed sub-sector remains underdeveloped and fragmented, resulting in a growing dependence on imported seeds. This situation underscores the need for a better understanding of the resource use efficiency and profitability of the domestic rice seed sub-sector, which was explored through semi-structured interviews conducted with 223 growers across two major rice seed production clusters in the Chitwan district, Nepal. For this, a purposive sampling approach was initially employed to select the district and clusters, followed by a simple random sampling of growers within each cluster. Profitability was assessed using cost-benefit analysis, while resource use efficiency (RUE) was evaluated through Cobb-Douglas regression. The results revealed a benefit-cost ratio of 1.85, indicating rice seed production is a profitable enterprise. The RUE analysis revealed that increasing the seed rate and agro-chemicals use by 98% and 90%, respectively, could improve efficiency, also reducing human labor, tillage, and irrigation by 16%, 209%, and 113%, respectively also optimizes the resource use. The study recommends increasing the use of quality seeds and agrochemicals while at the same time minimizing costs related to labor, tillage, and irrigation to enhance efficiency in the rice seed sector. The findings from this study can play a pivotal role in increasing profitability and optimizing resource use in the rice seed sub-sector of Nepal by providing an important policy guideline which can increase the domestic seed production and reduce the reliance on imported rice seeds. Further research is recommended to identify constraints to efficient resource use and to conduct a comparative economic analysis of adopting alternative technologies.